99 Type III and V AC joint dislocation show no difference in functional outcome and risk of surgery at 1-year follow-up. (25th January 2023) - Haugaard, Kristine; Bak, Klaus; Ryberg, Dorthe; Muharemovic, Omar; Hölmich, Per; Barfod, Kristoffer Weisskirchner
Abstract : Introduction: Acromioclavicular(AC) joint dislocations are common injuries, but the need for surgery is debated. The objective of the study was to evaluate the result after acute Rockwood type III and V AC joint dislocations managed non-surgically with the option of delayed surgical intervention. Materials and Methods: This was a prospective cohort study with clinical, radiological and patient-reported outcome assessment at baseline and 6w, 3m, 6m and 1y after acute AC joint dislocation. Inclusion criteria were patients aged 18–60 with acute AC joint dislocation and >50% superior displacement of the clavicle. All patients were treated non-surgically with 3 months of home-based training and with the option of delayed surgical intervention. At baseline, patients were graded as Rockwood type III or V based on the coracoclavicular difference. The primary outcome was the Western Ontario Shoulder Instability Index (WOSI). Secondary outcome was surgery yes/no. Results: Ninety-five patients, male:female ratio 9.6:1, mean age 39.5 (range 18–59), were included. 57 patients were Rockwood type III and 38 patients were type V. There were no statistically significant differences in WOSI between patients with type III and V injuries at any time-point. Nine patients (9.5%) were referred for surgery at an average of 189 days (range 75–358) after the injury; 7 type III and 2 type V (p=0.31). Patients eventually referred for surgery had significantly worse WOSI at 6w, 3m and 6m. Conclusion: Non-surgical management of Rockwood type III and V injuries shows similar and overall satisfactory results with 91% recovering well without the need of surgery.